2006
DOI: 10.1097/01.fpc.0000182778.03180.f3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of nonsteroidal anti-inflammatory drugs on colorectal adenomas is modified by a polymorphism in peroxisome proliferator-activated receptor δ

Abstract: This study confirms the protective effect of NSAIDs and suggests a modulating effect of a SNP in the promoter of PPARdelta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
4
25
2
Order By: Relevance
“…In spite of these indications, however, whether PPARd is a good target for chemoprevention and/or treatment of CRC remains controversial. It has been reported that a polymorphism in PPARd modifies the protective effects of nonsteroidal anti-inflammatory drugs on colorectal adenomas (Siezen et al, 2006), but other investigators have not reached the same conclusions in the context of CRC (McGreavey et al, 2005). As mentioned in the Introduction, PPARd was found to be unnecessary for small intestinal polyp formation (Barak et al, 2002), but PPARd attenuated polyp formation in chemical and genetic models (Harman et al, 2004;Reed et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In spite of these indications, however, whether PPARd is a good target for chemoprevention and/or treatment of CRC remains controversial. It has been reported that a polymorphism in PPARd modifies the protective effects of nonsteroidal anti-inflammatory drugs on colorectal adenomas (Siezen et al, 2006), but other investigators have not reached the same conclusions in the context of CRC (McGreavey et al, 2005). As mentioned in the Introduction, PPARd was found to be unnecessary for small intestinal polyp formation (Barak et al, 2002), but PPARd attenuated polyp formation in chemical and genetic models (Harman et al, 2004;Reed et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The conflicting result of the association between rs2910164 and PAH could be attributed to the distinct genotype frequency in different ethnic populations (e.g., the rs2910164 G allele in Caucasians: 76.58 vs Asians: 47.88%) [30]. Several other polymorphisms within the pathway of COX-2 production, including rs20417, rs20432, rs5275 and rs4648310, have been proven to be functional and are associated with a risk of various human diseases [31,32,33,34,35,36,37,38]. They might also be responsible for the development of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin has an added advantage of being readily available and inexpensive. Some epidemiologic studies have found an association between the consumption of aspirin and a reduced risk of many cancers, including EOC (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%